The aesthetics of care : on the literary treatment of animals - Donovan, Josephine, 1941- (New York : Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2016)
"In this important new book from a distinguished scholar, Josephine Donovan develops a new aesthetics of care, which she establishes as the basis for a critical approach to the representation of animals in literature. The Aesthetics of Care begins with a guide to the relationship between ethics and aesthetics, leading to a reconceptualization of key literary critical terms such as mimesis and catharsis, before moving on to an applied section, with interpretations of the specific treatment of animals handled by a wide range of authors, including Willa Cather, Leo Tolstoy, George Sand, and J.M. Coetzee. The book closes with three concluding theoretical chapters. Clear, original, and provocative, The Aesthetics of Care introduces and makes new contributions to a number of burgeoning areas of study and debate: aesthetics and ethics, critical theory, animal ethics, and ecofeminist criticism."--Publisher's description.
The aesthetics of modernity -- Willa Cather's aesthetic transitions -- The aesthetics of care -- Animal ethics and literary criticism -- Tolstoy's animals -- Local-color animals -- Coetzee's animals -- Metaphysical meat: "becoming men" and animal sacrifice -- The transgressive sublime, katharsis, and animal sacrifice -- Caring to hear, caring to see: art as emergence.
Includes bibliographical references and index.
Keywords: Animals in literature; Animal welfare in literature; Literature, Modern -- 19th century -- History and criticism; Literature, Modern -- 20th century -- History and criticism; Ecocriticism